2011
DOI: 10.1016/j.iilr.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the information seeking behavior of Greek graduate students: A case study set in the University of Macedonia

Abstract: This paper describes a survey designed to determine the information seeking behavior of graduate students at the University of Macedonia (UoM). The survey is a continuation of a previous one undertaken in the Faculties of Philosophy and Engineering at the Aristotle University of Thessaloniki (AUTh). This paper primarily presents results from the UoM survey, but also makes comparisons with the findings from the earlier survey at AUTh. The 254 UoM students responding tend to use the simplest information search t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Information literacy has become one of the cornerstones of librarians' activities, probably even more today than before owing to the critical need to be able to search the vast mass of digital resources available today, and evaluate it properly. The literature abounds of reports that a majority of today's students, including doctoral students, regard themselves as expert users in Web searching and proficient users of library-supported resources (Malliari et al 2013). Paradoxically, the literature also emphasises students' struggle with searching library resources, particularly when it comes to developing efficient search strategies, as we reported earlier in the paper.…”
Section: Is There a Role For Librarians?mentioning
confidence: 82%
See 2 more Smart Citations
“…Information literacy has become one of the cornerstones of librarians' activities, probably even more today than before owing to the critical need to be able to search the vast mass of digital resources available today, and evaluate it properly. The literature abounds of reports that a majority of today's students, including doctoral students, regard themselves as expert users in Web searching and proficient users of library-supported resources (Malliari et al 2013). Paradoxically, the literature also emphasises students' struggle with searching library resources, particularly when it comes to developing efficient search strategies, as we reported earlier in the paper.…”
Section: Is There a Role For Librarians?mentioning
confidence: 82%
“…Malliari et al (2013) found in their study at a Greek University that, overall, 11% of postgraduate students regarded 'consulting a librarian' as a common practice when starting a search; in practice, it appeared that 38% of the postgraduate respondents had actually never sought help from a librarian and only 25% had asked for help in the last six months of the period studied. Barriers that refrain doctoral students from asking help from librarians are manifold and varied.…”
Section: Is There a Role For Librarians?mentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies indicate that university websites, including websites of university libraries, are among the most widely used sources of information, and materials contained on these websites are important support for students in their learning (Biddix et al, 2011;Holman, 2011;Jones, Johnson-Yale, Millermaier, & Pérez, 2008;Kim, 2011;Malliari, Korobili, & Zapounidou, 2011;Simões & Soares, 2010;Van Scoyoc & Cason, 2006). According to Wu and Chen (2012), graduate students of one Taiwanese university preferred to use the university library website as their primary search source rather than the Internet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malliari et al (2011), Nicholas et al (2008, and Swain (2010) explored gender differences. Similarities and differences between undergraduate and graduate students in the use of e-books and e-journals were examined by Kaur and Verma (2009), Shelburne (2009), and Shuling (2007.…”
Section: Literature Reviewmentioning
confidence: 99%